OPTIMALISASI PENENTUAN POSISI SUDUT PANEL SURYA DALAM KEADAAN STATIS DAN DINAMIS - Taufiq Hidayat; Abdul Halim Daulay; Masthura Masthura (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Research has been carried out which aims to produce a solar panel positioning system based on the Arduino microcontroller, and to find out the optimal power measurement results based on the position of the solar panels. The research tools used in this research were the Arduino microcontroller as a tracking system, the LDR sensor as a tracker of the sun's movement, the MG966R servo motor as an actuator or driving system to follow the sun's tracks, and a 5 WP solar panel as a light source. The approach or method used in this study is scientific, namely an approach based on science and technology. The test method used is the direct test method. In a system that has been successfully designed, four LDR sensors act as input data which will be converted as tracking. From the test results of the Dual axis solar tracker the average voltage without and with the tracking system is 7.74 volts and 8.56 volts with the average current without and with the tracking system being 0.35 A and 0.44 A. The optimal angle obtained based on testing using the system is in the second test phase where the angle formed is 84 with a voltage obtained of 9.4 V and a current of 0.53 A with the power generated is 4.10 Watt